Current geotechnical engineering aspects of civil infrastructures : proceedings of the 5th GeoChina International Conference 2018 -- civil infrastructures confronting severe weathers and climate changes: from failure to sustainability, held on July 23 to 25, 2018 in HangZhou, China /: proceedings of the 5th GeoChina International Conference 2018 -- civil infrastructures confronting severe weathers and climate changes: from failure to sustainability, held on July 23 to 25, 2018 in HangZhou, China. ([2019]) - Unknown
No abstract available